2011
DOI: 10.1021/ol1028805
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Haloetherification by Asymmetric Opening of meso-Halonium Ions

Abstract: A new approach to enantioselective haloetherification reactions via desymmetrization of in situ-generated meso-halonium ions is described. The combination of N-haloamides as a halogen source and sodium salts of chiral phosphoric acids as catalysts can be used for the cyclization of symmetrical ene-diol substrates, yielding the haloetherification products under practical conditions in enantioenriched form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(64 citation statements)
references
References 45 publications
1
61
0
2
Order By: Relevance
“…Using the sodium salt of phosphate catalyst 1b and N -haloamides as a halogen source, the enantioselective haloetherification of ene-diol substrates was achieved via the desymmetrization of meso-halonium ions (Scheme 19b). [74] The same enantioselectivity was observed regardless of whether the 1b •Na salt was preformed or generated in situ from the phosphoric acid catalyst and sodium carbonate. Small changes in enantioselectivity were observed with different metal counterions (Li, 56% ee; Na, 62% ee; K, 46% ee).…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 83%
“…Using the sodium salt of phosphate catalyst 1b and N -haloamides as a halogen source, the enantioselective haloetherification of ene-diol substrates was achieved via the desymmetrization of meso-halonium ions (Scheme 19b). [74] The same enantioselectivity was observed regardless of whether the 1b •Na salt was preformed or generated in situ from the phosphoric acid catalyst and sodium carbonate. Small changes in enantioselectivity were observed with different metal counterions (Li, 56% ee; Na, 62% ee; K, 46% ee).…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 83%
“…This concept was validated recently by the demonstration of moderate enantioselectivity in the opening of meso bromonium ions in the presence of a chiral sodium phosphate. 6 Moreover, related studies in these laboratories demonstrated that the rates of Lewis base catalyzed seleno- and bromocycloetherification were greatly enhanced by the addition of Brønsted acids. 5,7 We hypothesized that, as a consequence of assisting in the Lewis base activation of the bromine source, the conjugate base of a sufficiently strong Brønsted acid would replace succinimide as the counterion of the bromonium intermediate (Scheme 1).…”
mentioning
confidence: 99%
“…17 Hennecke and coworkers recently reported a promising organocatalytic approach to haloetherfications by desymmetrization of in situ-generated meso-halonium ions (Scheme 14). 18 By treatment of symmetrical diol with chiral phosphoric acid salt in the presence of electrophilic iodine source 73, enantioenriched ether product 74 was obtained under the practical reaction conditions. The bromoetherification of 75 using NBS also gave good yield with ee up to 67%.…”
Section: Baldwin's Rules For Ring Closurementioning
confidence: 99%